Development of acid-base chemistry student activity sheet to improve metacognitive skills in Senior High School - Almira Nindya Divamita; Utiya Azizah (Jurnal Pijar Mipa, 2022)
This study aimed to determine the feasibility of STUDENT ACTIVITY SHEET SAS to improve students' metacognitive skills on the acid-base subject. The research used a 4-D development model. Data were collected through interviews, questionnaires, observation, and written tests. The research subjects were 36 students in class eleventh Science at the 5 Senior High School Madiun, East Java, Indonesia. The study used one pre-test and post-test control group design. Results showed that: 1) The average percentage of validity is 87%, which is categorized as very valid 2) The average percentage of practicality, which includes the results of student response questionnaires and student activity observations, is 94% and 100%, respectively, which both of them are categorized as very good; and 3) The n-gain of effectivity, which includes the results of the pre-test-post-test cognitive and metacognitive skills are 0.57 and 0.62, respectively. The inventory questionnaire resulted in a value of 94%, which is categorized as very good, and the observation of metacognitive skills resulted in 100% with very good criteria.